Multisystem Inflammatory Syndrome with Features of Atypical Kawasaki Disease during the COVID-19 Pandemic - Reza Shahriarirad; Anahita Sanaei Dashti; Shabnam Hajiani Ghotbabadi (Hindawi Limited, 2021)
Background. Although Kawasaki disease (KD) is the most common self-limited systemic vasculitis in pediatrics, the exact etiology of the disease, its association with other diseases, and pathogens is still unknown. In order to achieve a better understanding and management of the disease, documentation and reporting of atypical cases is justified, particularly with the growing number of children with inflammatory syndrome with clinical features simulating KD during the COVID-19 pandemic. Here, we present a case of an atypical case of KD presenting as multisystem inflammatory syndrome (MIS) during the COVID-19 pandemic. Case Presentation. The patient is a 7-year-old girl who developed fever (39°C) and erythematous multiform rash on the abdomen and along with erythema and edema on the extremities. Laboratory evaluation revealed neutrophilia and lymphopenia along with elevated C-reactive protein, erythrocyte sedimentation rate, troponin, lactate dehydrogenase, ferritin, and D-dimer. Although the patient did not fulfill the KD criteria, based on approved guidelines and approaches regarding atypical KD and multisystem inflammatory syndrome in children (MIS-C) during the COVID-19 pandemic, intravenous immunoglobulin along with aspirin was administered for the patients. The patient's symptoms resolved with an uneventful postdischarge course. Conclusion. Early diagnosis and treatment of patients meeting full or partial criteria for KD are critical to preventing end-organ damage and other long-term complications, especially during times of public crisis and global health emergencies, such as the novel coronavirus pandemic.